Field measurements of biogenic volatile organic compounds in the atmosphere by dynamic solid-phase microextraction and portable gas chromatography-mass spectrometry. (August 2015) - Barreira, Luís Miguel Feijó; Parshintsev, Jevgeni; Kärkkäinen, Niina; Hartonen, Kari; Jussila, Matti; Kajos, Maija; Kulmala, Markku; Riekkola, Marja-Liisa
Abstract: Biogenic volatile organic compounds (BVOCs) participate in many physicochemical processes in the atmosphere. Studies indicate that some of these volatile compounds can be photo-oxidized to non-volatile species that contribute to atmospheric formation and growth of secondary organic aerosols (SOA). In this study, the applicability of dynamic solid-phase microextraction (SPME) for the sampling of atmospheric BVOCs and their oxidation products was tested. These compounds were then analysed via portable gas chromatography-mass spectrometry (GC–MS). The measurements were performed in mid-summer 2013 at the Station for Measuring Ecosystem–Atmosphere Relations, SMEAR II in Hyytiälä, Finland. Numerous classes of compounds were efficiently sampled on PDMS/DVB coated SPME, thermally desorbed and analysed by GC–MS, including monoterpenes, their oxidation products, and amines. Results were analysed against meteorological conditions observed during the sampling campaign and the total amount of monoterpenes obtained by proton-transfer-reaction mass spectrometry (PTR-MS). The comparison of the referred data with obtained results demonstrated the capability of the dynamic SPME method for fast in-situ sampling and analysis of organic gaseous compounds in the atmosphere with minimal analytical steps. Highlights: Dynamic SPME sampling and portable GC–MS were utilized for analysis of VOCs in air. Study included preliminary identification of dimethylamine and ethylamine. SPME-GC-MS for field measurement of VOCs and their oxidation products was verified. Results correlated well with PTR-MS and meteorological data.